Influences of Mental Illness, Current Psychological State, and Concussion History on Baseline Concussion Assessment Performance. Issue 7 (June 2018) - Weber, Michelle L.; Dean, John-Henry L.; Hoffman, Nicole L.; Broglio, Steven P.; McCrea, Michael; McAllister, Thomas W.; Schmidt, Julianne D.; ,; Hoy, April Reed; Hazzard, Joseph B.; Kelly, Louise A.; Ortega, Justus D.; et al.
Background: A student-athlete's mental state, including history of trait anxiety and depression, or current psychological state may affect baseline concussion assessment performance. Purpose: (1) To determine if mental illness (anxiety, depression, anxiety with depression) influences baseline scores, (2) to determine if psychological state correlates with baseline performance, and (3) to determine if history of concussion affects Brief Symptom Inventory–18 (BSI-18) subscores of state anxiety, depression, and somatization. Study Design: Cross-sectional study; Level of evidence, 3. Methods: A sample of 8652 collegiate student-athletes (54.5% males, 45.5% females) participated in the Concussion Assessment, Research and Education (CARE) Consortium. Baseline assessments included a demographic form, a symptom evaluation, Standardized Assessment of Concussion, Balance Error Scoring System, a psychological state assessment (BSI-18), and Immediate Post-concussion Assessment and Cognitive Test. Baseline scores were compared between individuals with a history of anxiety (n = 59), depression (n = 283), and anxiety with depression (n = 68) and individuals without a history of those conditions (n = 8242). Spearman's rho correlations were conducted to assess the relationship between baseline and psychological state subscores (anxiety, depression, somatization) (α = .05). Psychological state subscores were compared between individuals with a self-reported history of concussions (0, 1, 2, 3, 4+) using Kruskal-Wallis tests (α = .05). Results: Student-athletes with anxiety, depression, and anxiety with depression demonstrated higher scores in number of symptoms reported (anxiety, 4.3 ± 4.2; depression, 5.2 ± 4.8; anxiety with depression, 5.4 ± 3.9; no anxiety/depression, 2.5 ± 3.4), symptom severity (anxiety, 8.1 ± 9.8; depression, 10.4 ± 12.4; anxiety with depression, 12.4 ± 10.7; no anxiety/depression, 4.1 ± 6.9), and psychological distress in state anxiety (anxiety, 3.7 ± 4.7; depression, 2.5 ± 3.6; anxiety with depression, 3.8 ± 4.2; no anxiety/depression, 0.8 ± 1.8), depression (anxiety, 2.4 ± 4.0; depression, 3.2 ± 4.5; anxiety with depression, 3.8 ± 4.8; no anxiety/depression, 0.8 ± 1.8), and somatization (anxiety, 2.3 ± 2.9; depression, 1.8 ± 2.8; anxiety with depression, 2.2 ± 2.4; no anxiety/depression, 0.9 ± 1.7). A moderate positive relationship existed between all BSI-18 subscores and total symptom number (n = 8377; anxiety: r s = 0.43, P < .001; depression: r s = 0.42, P < .001; somatization: r s = 0.45, P < .001), as well as total symptom severity (anxiety: r s = 0.43, P < .001; depression: r s = 0.41, P < .001; somatization: r s = 0.45, P < .001). Anxiety, depression, and somatization subscores were greater among student-athletes that self-reported more concussions. Conclusion: Clinicians should be cognizant that student-athletes with a history of trait anxiety, depression, and anxiety with depression may report higher symptom score and severity at baseline. Individuals with extensive concussion history may experience greater state anxiety, depression, and somatization.